Contemporary Interpretation with Classical Insight: Gender View of Al-Shanqiti's Tafsir Adwa' Al-Bayan - Putra, D.I. Ansusa (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
Classical and contemporary interpreters have different insights into the interpretation of the Quran, especially on gender issues. As a contemporary interpreter, Al-Shanqiti's interpretation is unique in involving periodizations and complex social settings. This article aims to examine the interpretation of the Qur'an al-Shanqiti in its Tafseer adwa' al-Bayan. Al-Shanqity's interpretation is studied with the type of literature research through al-Shanqiti's interpretation data, especially related to gender issues which are briefly compared with other contemporary gender interpretations. This article uses a descriptive-content analysis method with primary research data, namely: Tafsir Adwa' al Bayan. The article finds that, as a contemporary scholar, al-Shanqity directed his interpretation to classical insights because of its orientation that adapted to the social setting in which he lived. These results conclude a more general conclusion that if the social orientation of the interpreter refers tovm the classical context, then the resulting interpretation also has classical nuances even though he lives in the contemporary era. So it can be understood that interpretation is a representation of the orientation and social setting of the interpreter. This article explains further research about the different interpretations of the Qur'an so that it becomes a basis for identifying cross-epoch interpretation products with their respective characters, orientations, and social settings.